Comprehensive Analysis of Multi-Omics Data on RNA Polymerase as an Adverse Factor in Head and Neck Squamous Cell Carcinoma - Gu YJ; Zhang J; Liu YJ; Zhang Q; Geng QF (Journal of Inflammation Research)
Yu-Jia Gu,1,* Jie Zhang,2,* Yuan-Jie Liu,3 Qian Zhang,4 Qi-Feng Geng1 1The Fifth Outpatient Department, Nanjing Stomatological Hospital, Affiliated Hospital of Medical School, Institute of Stomatology, Nanjing University, Nanjing, Jiangsu, 210029, People’s Republic of China; 2Department of Gynecology, Jiangsu Province Hospital and Nanjing Medical University First Affiliated Hospital, Nanjing, Jiangsu, 210029, People’s Republic of China; 3Department of Oncology, Affiliated Hospital of Nanjing University of Chinese Medicine, Jiangsu Province Hospital of Chinese Medicine, Nanjing, Jiangsu, 210029, People’s Republic of China; 4No. 1 Clinical Medical College, Nanjing University of Chinese Medicine, Nanjing, Jiangsu, 210023, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qi-Feng Geng, Email 20220071@njucm.edu.cnBackground: High transcription levels are essential for cancer cells to maintain their malignant phenotype. While RNA polymerases (POLRs) have been implicated in various transcriptional mechanisms, their impact on the tumor microenvironment (TME) remains poorly understood.Methods: We analyzed publicly available pan-cancer cohorts to evaluate the expression and genomic alterations of POLRs. Focusing on head and neck squamous cell carcinoma (HNSC), we integrated bulk RNA sequencing, single-cell, and spatial transcriptome data to identify POLR2C expression patterns and its potential regulation by Yin Yang 1 (YY1). In vitro and in vivo experiments were conducted to validate the functional role of the YY1-POLR2C axis in cancer proliferation and immune modulation.Results: POLRs were found to be aberrantly expressed in cancers and associated with genomic alterations. In HNSC, POLR up-regulation was linked to poor prognostic features. POLR2C was significantly up-regulated in malignant cells, and its expression appeared to be transcriptionally regulated by YY1. Functional studies demonstrated that the YY1-POLR2C axis drives cell-cycle dysregulation and malignant proliferation in HNSC. Additionally, high POLR expression negatively correlated with immune cell infiltration and facilitated immune evasion. Mechanistically, POLRs mediated frequent interactions between malignant and immune cells, potentially contributing to resistance to immunotherapy.Conclusion: This study highlights the dual role of POLRs in promoting malignant proliferation and shaping an immunosuppressive TME. POLR2C, regulated by YY1, emerges as a critical mediator in HNSC and a promising target for precision therapies.Keywords: head and neck squamous cell carcinoma, RNA polymerases, multi-omics analysis, immunosuppression, YY1 transcription factor, tumor microenvironment